High-amylose wheat bread with reduced in vitro digestion rate and enhanced resistant starch content. (February 2022) - Li, Caili; Dhital, Sushil; Gidley, Michael J.
Abstract: High amylose wheat flour (HAWF) is a relatively new food ingredient, with potential for enhanced nutritional functionality of slower digestion and greater resistant starch levels compared to wild-type wheat flour (WTWF) products. This study focusses on the role of amylose content in the baking process and eating qualities of bread, made using an industry-standard rapid dough method. DSC, XRD and polarized light microscopy were used to monitor changes of ordered structure in starch after baking, and showed more retained crystalline structure in the high-amylose wheat bread (HAWB) than wild-type wheat bread (WTWB). Moreover, HAWB had lower loaf volume, more dense crumb structure, as well as higher hardness than WTWB. These starch structural and local density features subsequently lead to bread made with 100% or 50% HAWF being more resistant to enzyme hydrolysis compared to WTWB. Resistant starch levels were significantly increased by ∼11 and 12 times in bread made using 100% HAWF with amylose content 71% and 84% respectively, and ∼6 times in bread prepared with 50% incorporation HAWF (84% AM) than WTWB. The nutritional and physical properties of bread are highly correlated to starch amylose content (AM), starch thermal properties and crumb hardness, with AM playing the leading role. This study identifies the structural basis for flour amylose content effects in baking and nutritional functionality and can help guide development of nutritionally-enhanced foods with HAWF. Graphical abstract: Image 1 Highlights: Amylose plays an essential role in determining bread texture and in-vitro digestibility. 50% high amylose wheat inclusion increases resistant starch 6 times. High amylose wheat breads are harder but 50% inclusion is comparable to wild type. Crystal structure is retained more in high amylose bread. Nutritional functionality of bread can be enhanced with inclusion of HAWF.